2013
DOI: 10.1673/031.013.2401
|View full text |Cite
|
Sign up to set email alerts
|

Responses of an Aphidophagous Ladybird Beetle,AnegleisCardoni, to Varying Densities ofAphis gossypii

Abstract: Laboratory experiments were conducted to determine the functional and numerical responses of fourth instar larvae, adult male, and adult female ladybird beetles, Anegleis cardoni Weise (Coleoptera: Coccinellidae), to different densities of aphids, Aphis gossypii Glover (Hemiptera: Aphididae), on the bottle gourd, Lagenaria vulgaris Seringe (Cucurbitales: Cucurbitaceae). The results revealed a density dependent, Type II functional response of A. cardoni. Prey consumption increased curvilinearly with an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
6
16
0
Order By: Relevance
“…Similar findings were also reported by Omkar and Kumar (2013) in the management strategies of A. cordoni against mustard aphid. Omkar et al, (2009) further reported that the performance of A. cardoni was preydependent and the order of suitability of the prey tested was A. gossypii > A. craccivora > L. erysimi.…”
Section: Feeding Potential Of Anegleis Cardoni On Mustard Aphid L Ersupporting
confidence: 89%
“…Similar findings were also reported by Omkar and Kumar (2013) in the management strategies of A. cordoni against mustard aphid. Omkar et al, (2009) further reported that the performance of A. cardoni was preydependent and the order of suitability of the prey tested was A. gossypii > A. craccivora > L. erysimi.…”
Section: Feeding Potential Of Anegleis Cardoni On Mustard Aphid L Ersupporting
confidence: 89%
“…In the present study, negative linear coefficients (P 1 ) for conspecific and heterospecific groups of two females reveal that the rate of consumption of prey by these predators decreases with increase in abundance of prey, which indicate a Type II functional response (Bayoumy, 2011a, b;Osman & Bayoumy, 2011;Omkar & Kumar, 2013). The curves of the proportions of prey consumed by C7 + C7, Ct + Ct and C7 + Ct pairs of females are similar and appear to take the form of a decelerating type II functional response when provided with a low to optimal supply of prey, followed by an accelerating type III functional response when provided with an optimal to abundant supply of prey.…”
Section: Discussionsupporting
confidence: 49%
“…a sigmoidal functional response (e.g., Sarmento et al, 2007;Abdollahi et al, 2010;Bayoumy, 2011a). Several studies have evaluated the functional responses of particular species of lady beetles (Sarmento et al, 2007;Abdollahi et al, 2010;Bayoumy, 2011a;Osman & Bayoumy, 2011;Gupta et al, 2012;Omkar & Kumar, 2013) and the nature of their predator-predator interactions (synergistic /additive /antagonistic) within aphidophagous guilds (Losey & Denno, 1998, 1999Snyder & Ives, 2003;Costamagna et al, 2007;Snyder, 2009;Grez et al, 2007Grez et al, , 2011Grez et al, , 2012. However, studies of the functional response of species within predatory guilds (Omkar & Pervez, 2011;Jamour & Shishehbor, 2012;Vanacloacha et al, 2013) coupled with that of the interaction between predators are scanty (Snyder & Ives, 2003;Omkar & Pervez, 2011).…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations